Imagined Communities and Educational Possibilities : a Special Issue of the journal of Language, Identity, and Education. - Kanno, Yasuko (Taylor and Francis, 2012)
Imagined Communities and Educational Possibilities focuses on three main themes: imaged communities expand the range of possible selves, technological advances in the last two decades have had a significant impact on what is possible to imagine, and imagination at even the most personal level is related to social ideologies and hegemonies. The diverse studies in this issue demonstrate convincingly that learners and teachers are capable of imagining the world as different from prevailing realities. Moreover, time and energy can be invested to strive for the realization of alternative vis.